1998
DOI: 10.1183/09031936.98.12010030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life during formoterol treatment: comparison between asthma-specific and generic questionnaires. Canadian and the Dutch Formoterol Investigators

Abstract: This study aimed to investigate the effect of treating patients with moderate asthma with formoterol on quality of life (QoL) and to compare several questionnaires in their ability to detect changes in QoL. In an eight month multicentre, randomized, placebo-controlled trial, patients with asthma using daily inhaled corticosteroids and beta2-agonists (> or = 5 inhalations x week(-1)) were randomized to 6 months treatment with formoterol 24 microg b.i.d. (by Turbuhaler) or a matching placebo. Patients recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
2
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
2
18
2
1
Order By: Relevance
“…Other studies have also found that the average HRQL in mild-to-moderate asthma patients is close to that of the general population [24]. A strong link between asthma-related quality of life and disease severity has been reported [20,25], and this relationship was also observed in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…Other studies have also found that the average HRQL in mild-to-moderate asthma patients is close to that of the general population [24]. A strong link between asthma-related quality of life and disease severity has been reported [20,25], and this relationship was also observed in the current study.…”
Section: Discussionsupporting
confidence: 73%
“…However, the logarithmic mean scale score improved slightly but significantly in the second study. In previous studies, HQOLincreased slightly by 0.09 (1 1) or remained unchanged (1). Therefore the change in scale scores in this study was within the reported range of variation.…”
Section: Discussionsupporting
confidence: 51%
“…However, in the present study, a distribution approximating normal was found only in the logarithmic values and not in the raw scale scores. That frequency distribution of scale scores was not normally distributed was also recognized in the report by Molen et al (1). Wesuggest that comparison of distributions should be done in logarithmic values.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations